Automatización de almacenes: nuevas tecnologías - Puerta Salazar, Sharon (2021)
Today, fully automated warehouses are a reality, however, in order to understand this concept it is necessary to understand what industrial automation is, and how to use tools, such as Big Data, WMS (Warehouse Management System), RFID (Radio Frequency Identification) and dynamic racks, help companies to break through in this new world of constant change, showing their clear superiority compared to traditional methods such as the use of barcodes, fixed shelves, manual kardex controls, among others. In addition, the article shows the comparison between companies that make use of traditional warehouses and companies that have automated warehouses. Finally, this article makes evidence of the importance of having these new digital tools to be able to face the new demands of the market, which demands greater effectiveness in all business processes.